2012
DOI: 10.1016/j.cemconres.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A new class of organosilane-modified polycarboxylate superplasticizers with low sulfate sensitivity

Abstract: It is well-established that a competitive adsorption exists between polycarboxylate superplasticizers (SP) with soluble sulfate ions solubilized in interstitial solution of cement paste, which may causes a loss of dispersing properties depending on the cement composition. Early reports suggested that this incompatibility is due to competitive weak ionic interaction between functional acrylate groups and solubilized sulfate ions with cement grains. In this study, SPs including trialkoxysilane functional groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(58 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…The surface has not to be fully covered to have a high fluidity. As demonstrated by this study, previous results carried out with cement and superplasticizers have also shown a linear relationship between log(yield stress) [36][37][38] or the paste-flow [42][43][44] and the mass of adsorbed polymer on cement grains. More recently a similar linear relationship has been shown with a calcite suspension containing two PCEs which differ only by the repartition of the carboxylic monomer along the backbone [39].…”
Section: A Unique Fluidizing Efficiency For Carboxylate Superplasticisupporting
confidence: 63%
See 1 more Smart Citation
“…The surface has not to be fully covered to have a high fluidity. As demonstrated by this study, previous results carried out with cement and superplasticizers have also shown a linear relationship between log(yield stress) [36][37][38] or the paste-flow [42][43][44] and the mass of adsorbed polymer on cement grains. More recently a similar linear relationship has been shown with a calcite suspension containing two PCEs which differ only by the repartition of the carboxylic monomer along the backbone [39].…”
Section: A Unique Fluidizing Efficiency For Carboxylate Superplasticisupporting
confidence: 63%
“…5, the simplest way to link the yield stress with the adsorption for a defined paste formulation is the mass of adsorbed polymer. It is noteworthy that several experimental studies have already previously reported a linear relationship between the logarithm of the yield stress and the mass of adsorbed polymer [36][37][38][39]. Aside from the point without superplasticizer, the relationship is nearly linear until 0.3 mg/m 2 and diverges slightly after.…”
Section: Surface Coverage/mass Of Adsorbed Polymermentioning
confidence: 87%
“…layered calcium organosilicate hybrids with covalently linked organic functionalities [87,88]. The original observation that silylated hydrosoluble polymers can be covalently bonded to calcium silicate hydrate [89] led to a detailed study of polycarboxylate-based superplasticizers modified with trialkoxysilane functions synthesized by radical copolymerization [90]. The authors observed that that a partial substitution of carboxyl by trialkoxysilane groups enhances the adsorption; however, an excess of silylated functions can be detrimental for adsorption.…”
Section: Effect Of Chemical Admixturesmentioning
confidence: 99%
“…For example, it has been shown that the well-known sensitivity of PCEs to sulfates can be decreased by adding silyl functions in a methacrylic-based backbone. 72,73 Also, using totally different monomers in the backbone, as it is the case for amphoteric PCEs, is reported to improve the adsorption onto the negatively charged surfaces of silicates and/or onto special types of cement. 74,75 Such modifications that include introducing alternative monomers and/or macromonomers can clearly modify PCEs adsorption ability in three different ways.…”
Section: Sidebar 1 Pce Structure and Chemistrymentioning
confidence: 99%
“…They include, for example, the impact of overall PCE conformation both in the solution and on the surface. Finally, in the presence of other species PCEs may be sensitive to competitive adsorption, 22,72,73 a process in which both molecular and submolecular scale effects play a role. 53,67 These are simple examples of how the properties of a PCE may change with the chemical nature of its components and only represent a small insight into the broad range of possible modifications of PCEs.…”
Section: Sidebar 1 Pce Structure and Chemistrymentioning
confidence: 99%